A surface wave elastography technique for measuring tissue viscoelastic properties. (April 2017) - Zhang, Xiaoming
Highlights: A surface wave elastography method is proposed to study the viscoelastic properties of skin by measuring the surface wave speed and wave attenuation on the skin. Experiments were carried out on porcine skin tissues. The tissues had lower wave speed at body temperatures than that at room temperature. Material decayed tissues had higher wave speed and wave attenuation. Abstract: A surface wave elastography method is proposed to study the viscoelastic properties of skin by measuring the surface wave speed and attenuation on the skin. Experiments were carried out on porcine skin tissues. The surface wave speed is measured by the change of phase with distance. The wave attenuation is measured by the decay of wave amplitude with distance. The change of viscoelastic properties with temperature was studied at room and body temperatures. The wave speed was 1.83 m/s at 22 °C but reduced to 1.52 m/s at 33 °C. The viscoelastic ratio was almost constant from 22 °C to 33 °C. Fresh and decayed tissues were studied. The wave speed of the decayed tissue increased from 1.83 m/s of fresh state to 2.73 m/s. The viscoelastic ratio was 0.412/mm at the decayed state compared to 0.215/mm at the fresh state. More tissue samples are needed to study these viscoelastic parameters according to specific applications.